Epidemiological, Clinical, and Radiological comparison of adult and Pediatric features in COVID-19: A Scoping Review - Parkar, Sadia; Pethani, Asma; Syeda Mah-e-Jabeen Zehra; Khan, Faheem Ullah; Kazi, Zaubina; Hilal, Kiran; Saleem, Ali Faisal (Journal of the Pakistan Medical Association, 2022)
Objective: To assess epidemiological, clinical, and radiological characteristics of the coronavirus disease in children and adults. Method: The scoping review comprised search on PubMed, Scopus Cochrane, and Google Scholar databases from January 2020 to April 2021 for English-language articles dealing with clinical and radiological manifestations amongst children and adults affected by coronavirus disease. Two reviewers independently screened the titles and abstracts. Results: Of the 389 studies initially identified, 39(10%) were reviewed in detail. Data suggested that children were less frequently affected by the coronavirus disease. The affected children showed milder disease with low case fatalities compared to the adults. Conclusions: There exists significant gaps in knowledge of clinical and radiological aspects of coronavirus disease, but the available scientific data showed that the disease seems to be unusual in children. Key Words: Children, COVID-19, SARS-CoV2, Epidemiology, Clinical, Radiological. Continuous...